EKSPLORASI BAKTERI ENTOMOPATOGENIK PENGENDALI HAMA Plutella xylostella DAN Spodoptera Sp. PADA TANAMAN KUBIS BUNGA DAN BROKOLI - Salaki, Christina L. (EUGENIA, 2011)
ABSTRACT   The research aimed to explore potential entomopathogenic bacteria as biological control agent for insect pest of P. xylostella and Spodoptera sp. in cabbage and broccoli. The indigenous bacteria were explored by taking 103 samples from location around North Sulawesi. Bacteria were selectively isolated by using Ohba and Aizawa method and then identified based on morphology. Subsequently the isolates were screened by their potency to kill test insect of P. xylostella and Spodoptera sp. The isolates were able to kill ≥ 50 % test insect considered  as potential for biological control. The potential isolates were then selected and would be developed  as powder and liquid bio-pesticide through large scale production. The result of the study showed that 145 Bacillus thuringiensis isolates and 202 Bacillus cereus isolates were obtained from 103 samples. The screening of the isolates based on standard test insect for cabbage and broccoli were in progress. The potential isolates would be further selected on the basis of their pathogenicity test. Based on pathogenecity test, chosen isolates will be developed as  bio-pasticide to control insect pest of cabbage and broccoli. Keywords : Exploration, entomopathogenic bacteria, biological control, Plutella xylostella, Spodoptera Sp.